2019
DOI: 10.1039/c8fo01575a
|View full text |Cite
|
Sign up to set email alerts
|

Cashew apple fiber prevents high fat diet-induced obesity in mice: an NMR metabolomic evaluation

Abstract: Dietary fiber intake plays an important role in the prevention of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 57 publications
(73 reference statements)
0
20
0
2
Order By: Relevance
“…As amilases produzem maltose, maltotriose, dextrinas e outros oligossacarídeos que são substratos de oligossacaridases e maltases, resultando em glicose (Murray et al, 1998). O AR e as fibras dietéticas podem reduzir a taxa de digestão e a atividade da enzima amilase prevenindo o aumento do nível de glicose, insulina e diminuindo a glicose plasmática pós-refeição (Carvalho et al, 2019). Como a maioria dos processos de síntese é induzida pela insulina, as diferenças no peso podem estar relacionadas às diferenças na insulinemia dos diferentes grupos (Petersen & Shulman, 2018).…”
Section: Resultsunclassified
“…As amilases produzem maltose, maltotriose, dextrinas e outros oligossacarídeos que são substratos de oligossacaridases e maltases, resultando em glicose (Murray et al, 1998). O AR e as fibras dietéticas podem reduzir a taxa de digestão e a atividade da enzima amilase prevenindo o aumento do nível de glicose, insulina e diminuindo a glicose plasmática pós-refeição (Carvalho et al, 2019). Como a maioria dos processos de síntese é induzida pela insulina, as diferenças no peso podem estar relacionadas às diferenças na insulinemia dos diferentes grupos (Petersen & Shulman, 2018).…”
Section: Resultsunclassified
“…CCK can inhibit the activity of hunger‐stimulating neuropeptide Y in the hypothalamus [8]. However, some NDPs can decrease the expression of ghrelin that induces hunger via acting on hypothalamic brain cells in the central nervous system [106]. Fermentable NDPs produce SCFAs that are importantly involved in the regulation and control of appetite and satiety through stimulation of hormonal and neural signals in various organs and tissues [107].…”
Section: Anti‐obesity Via Regulating Appetite and Satietymentioning
confidence: 99%
“…Various authors have reported the effect of the administration of cashew bagasse in murine models, such as the case of Carvalho et al (2017), who administered 10% of sonicated and lyophilized bagasse to a group of healthy rats, causing an increase in body weight and elevation of serum triglyceride and LDL cholesterol levels after 15 weeks. Later, Carvalho et al (2019) administered natural cashew fiber (IcF) and cashew fiber after undergoing a low molecular weight metabolite (cFSM) extraction process to obese male Swiss mice for 15 weeks. At the end of the treatment, a reduction in glycemia and serum levels of insulin and ghrelin was found, while the animals fed IcF showed hyperlipidemia, hyperleptinemia, and increased abdominal fat, concluding that the elimination of low molecular weight metabolites in cashew bagasse is correlated with the improvement of the health of obese mice.…”
Section: Uses and Applications Of Cashewmentioning
confidence: 99%